ORIENTASI POLA PENGASUHAN ANAK USIA DINI PADA KELUARGA MILITER DI ASRAMA KODAM KELURAHAN JATINGALEH CANDISARI SEMARANG (Universitas Negeri Semarang, 2013)
The research was conducted at Regional Military Family Military Boarding Village Jatingaleh Candisari Distric Semarang. The reason researchers do research on military families because of parental upbringing is different from other communities. The objectives of this study are: 1) Knowing how the orientation of early childhood parenting to military families in BoardingJatingaleh Urban District Military Command Candisari. 2) Knowing what are the values that apply to military families in Boarding Jatingaleh Urban District Military Command Candisari.Â Data collection methods used were participant observation methods to see what is done to the child and parent demographics and topography of the place of research, in-depth interviews relating to parenting that parents do to children, and documentation. The number of informants who studied there were 12 parents of children aged 0-6 years old and was taken from each Neighborhood Association.Â The results illustrate the orientation of parenting parents almost the same democratic parenting gives children the freedom to engage in activities that do no harm, there is no differencein educating children, the absence of parental punishment to the child and the cooperation in determining opinion. However, there are also parents who apply authoritarian parenting. These values are applied to the same parents are religious values, the value of modesty, cleanliness and value the value of beauty. Democratic parenting is not a perfect upbringing, so it should use the three parenting is democratic, authoritarian and permissive adapted to the circumstances.